The Liquid Light - Keeley, Bibo; Keeley, Brian (Ars Medica, 2023)
The Liquid Light is an autobiographical text by artist duo Bibo Keeley and Brian Keeley, which reflects on their shared experience of Brian's critical illness and eventual heart transplant in 2013. The first section is in the form of extracts from their longer accounts of that time, followed by a reflection on the impact of their experiences on their creative practice. Bibo’s contemporaneous account was written in the form of diary letters to Brian while he was in Intensive Care following a heart attack and subsequent multi-organ failure, not knowing if he would survive to read them. In 2014, In the early months of Brian's recovery after receiving a heart transplant, he also wrote a detailed account of his memories of months in hospital from a patient perspective, when for most of the time he had been critically ill and unable to communicate verbally. Neither Brian nor Bibo would read each other’s words until some years later. Their two distinct perspectives offer an insight into their emotions and fears, and how they lived through precarious and unpredictable times. The extracts focus on the day of the transplant, and the immediate aftermath. In the second section Bibo and Brian discuss their more recent creative practice - specifically their moving image/photography projects in which they have explored themes relating to their past experiences and their ongoing lives. Their themes include memory and trauma, the impact of the legacy of organ transplantation on their everyday life, and drawing parallels between the fragility of human life and that of the natural environment.